Spatiotemporal Characteristics of the Largest HIV-1 CRF02_AG Outbreak in Spain: Evidence for Onward Transmissions - Kostaki, Evangelia-Georgia; Flampouris, Andreas; Karamitros, Timokratis; Chueca, Natalia; Alvarez, Marta; Casas, Paz; Alejos, Belen; Hatzakis, Angelos; Garcia, Federico; Paraskevis, Dimitrios; , CoRIS; Moreno, Santiago; et al. (Frontiers in Microbiology, 2019)
Background and Aim: The Circulating Recombinant Form 02_AG (CRF02_AG) is the predominant clade among the Human Immunodeficiency Virus type-1 (HIV-1) non-Bs with a prevalence of 5.97% (95% CI: 5.41%-6.57%) across Spain. Our aim was to estimate the levels of regional clustering for CRF02_AG and the spatiotemporal characteristics of the largest CRF02_AG subepidemic in Spain. Methods: We studied 396 CRF02_AG sequences obtained from HIV-1 diagnosed patients during 2000-2014 from 10 autonomous communities of Spain. Phylogenetic analysis was performed on the 391 CRF02_AG sequences along with all globally sampled CRF02_AG sequences (N=3,302) as references. Phylodynamic and phylogeographic analysis was performed to the largest CRF02_AG monophyletic cluster by a Bayesian method in BEAST v1.8.0 and by reconstructing ancestral states using the criterion of parsimony in Mesquite v3.4, respectively. Results: The HIV-1 CRF02_AG prevalence differed across Spanish autonomous communities we sampled from (p<0.001). Phylogenetic analysis revealed that 52.7% of the CRF02_AG sequences formed 56 monophyletic clusters, with a range of 2 to 79 sequences. The CRF02_AG regional dispersal differed across Spain (p=0.003), as suggested by monophyletic clustering. For the largest monophyletic cluster (subepidemic) (N=79), 49.4% of the clustered sequences originated from Madrid, while most sequences (51.9%) had been obtained from men having sex with men (MSM). Molecular clock analysis suggested that the origin (tMRCA) of the CRF02_AG subepidemic was in 2002 (median estimate; 95% Highest Posterior Density-HPD: 1999-2004). Additionally, we found significant clustering within the CRF02_AG subepidemic according to the ethnic origin. Conclusions: CRF02_AG has been introduced as a result of multiple introductions in Spain, following regional dispersal in several cases. We showed that CRF02_AG transmissions were mostly due to regional dispersal in Spain. The hot-spot for the largest CRF02_AG regional subepidemic in Spain was in Madrid associated with MSM transmission risk group. The existence of subepidemics suggest that several spillovers occurred from Madrid to other areas. CRF02_AG sequences from Hispanics were clustered in a separate subclade suggesting no linkage between the local and Hispanic subepidemics.